2011
DOI: 10.1007/s13353-011-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutations and polymorphisms of the MC4R gene in Polish obese children and adolescents in relation to the relative body mass index

Abstract: Extensive studies of the MC4R gene polymorphism showed that, among numerous variants, there are mutations responsible for monogenic obesity, as well as polymorphisms negatively correlated with the risk of obesity. In this report, we present the first studies of the whole coding sequence of the MC4R gene in 243 Polish obese children and adolescents (the mean relative body mass index [RBMI] was 163.6). In addition, 101 non-obese adults were also analyzed. Direct sequencing facilitated the identification of six m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
1
4
2
1
Order By: Relevance
“…Interestingly, Val103Ile has been considered an obesity-protective polymorphism and was observed in both groups, being the most frequent variant identified in our sample (2.9%). This observation is similar to previous studies in a Polish cohort and a sample of the South American population 17,31,32. Wang et al31 have performed a meta-analysis using six East Asian studies, where they found that the frequency of this variant was 2.9% (n=19,882) in subjects with obesity and 3.9% (n=35,373) in nonobese individuals.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, Val103Ile has been considered an obesity-protective polymorphism and was observed in both groups, being the most frequent variant identified in our sample (2.9%). This observation is similar to previous studies in a Polish cohort and a sample of the South American population 17,31,32. Wang et al31 have performed a meta-analysis using six East Asian studies, where they found that the frequency of this variant was 2.9% (n=19,882) in subjects with obesity and 3.9% (n=35,373) in nonobese individuals.…”
Section: Discussionsupporting
confidence: 87%
“…In other independent studies in Spanish children the frequencies of this polymorphism were lower than in other European countries [43,44,45]. The frequency of the Ile251Leu variation in our studied sample was 5.04% (6 children with abdominal obesity), which is higher than the observed values in other Spanish and Polish pediatric populations [28,43,44]. Heterozygous subjects for the Ile251Leu SNP showed higher levels of total cholesterol and LDL-cholesterol.…”
Section: Discussioncontrasting
confidence: 76%
“…In some other studies, it was found that two MC4R variants are negatively correlated with the risk of obesity (27). These polymorphisms cause amino acid substitutions in codon 103 (V103I) and codon 251 (I251L) (27,28). Contrary to these findings, in our study V103I mutation was found equally in patients and controls and I251L mutation were not detected in both of the groups.…”
Section: Discussioncontrasting
confidence: 99%